Alteration of tissue expression of human beta defensin-1 and human beta defensin-2 in psoriasis vulgaris following phototherapy. (18th May 2020) - Uzuncakmak, Tugba Kevser; Karadag, Ayse Serap; Ozkanli, Seyma; Akbulak, Ozge; Ozlu, Emin; Akdeniz, Necmettin; Oguztuzun, Serpil
ABSTRACT: We compared the expression profiles of antimicrobial peptides (AMPs) in psoriatic skin before and after narrow band ultraviolet B (nb-UVB) phototherapy and compared the levels to healthy controls. We studied 15 male and 12 female patients with psoriasis vulgaris, and 11 female and nine male control individuals. The patient group was treated with 24–36 sessions of nb-UVB phototherapy. Immunohistochemical staining for human beta defensin 1 (hBD-1) and human beta defensin 2 (hBD-2) expression of lesioned and control skin was performed prior to and following phototherapy. After phototherapy, the psoriatic area and severity index (PASI) decreased significantly in the treated patients compared to controls. The hBD-1 level was significantly higher in psoriasis patients than healthy controls. We found no statistically significant difference in hBD-1 and hBD 2 levels before and after phototherapy in the patient group. Although hBD-1 plays a role in psoriasis, levels of human beta defensin 1 and 2 are not affected significantly by phototherapy.